Huge Pulmonary Artery Aneurysm - Aiman M Hammad; Sultan M Al-Qahtani; Mohammed A Al-Zahrani (Canadian Respiratory Journal)
Pulmonary artery aneurysms (PAAs) are uncommon entities. PAAs are caused mostly by trauma (often iatrogenic), infections and Behcet’s disease (BD). Less common causes are pulmonary hypertension, congenital heart disease and neoplasm. BD is a multisystem disorder presenting with recurrent oral and genital ulcerations, as well as ocular involvement, and PAA is one of its rare complications. A case of huge PAA, in which the usual criteria for the clinical diagnosis of BD were present, is described. Transcatheter embolization resulted in clinical improvement.